3(4x+6)=15x+5-3x+13

Simple and best practice solution for 3(4x+6)=15x+5-3x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x+6)=15x+5-3x+13 equation:


Simplifying
3(4x + 6) = 15x + 5 + -3x + 13

Reorder the terms:
3(6 + 4x) = 15x + 5 + -3x + 13
(6 * 3 + 4x * 3) = 15x + 5 + -3x + 13
(18 + 12x) = 15x + 5 + -3x + 13

Reorder the terms:
18 + 12x = 5 + 13 + 15x + -3x

Combine like terms: 5 + 13 = 18
18 + 12x = 18 + 15x + -3x

Combine like terms: 15x + -3x = 12x
18 + 12x = 18 + 12x

Add '-18' to each side of the equation.
18 + -18 + 12x = 18 + -18 + 12x

Combine like terms: 18 + -18 = 0
0 + 12x = 18 + -18 + 12x
12x = 18 + -18 + 12x

Combine like terms: 18 + -18 = 0
12x = 0 + 12x
12x = 12x

Add '-12x' to each side of the equation.
12x + -12x = 12x + -12x

Combine like terms: 12x + -12x = 0
0 = 12x + -12x

Combine like terms: 12x + -12x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3x-4-2x=2x-7 | | 2x+4x^2-8x^3= | | 15+2(3x+2)=3(7+2x) | | 4-4a=36 | | x^4-x^3-9x^2+3x-18=0 | | x-8x+12=23 | | 45=-5X-54 | | 95-m=72 | | 27=15+x+9 | | Y=-7(9)+8 | | a(2a+4b)= | | 7r^2+5r-2=0 | | p+21=15 | | 86=13x-5 | | 5x-123+8x=98 | | -10x+58=6x+41 | | 2x+3(x-3)=6x+1 | | 7-7(5m+2)=-147 | | 91=5x-24 | | 42+f=62 | | -37-8x+11x=17 | | -2(1)+8y=8 | | 3(n-2)=7n-7-4n | | .18(24)+.03x=0.06(24+x) | | 9*3=1(x+2) | | ax+18=3x-3b | | 1.5x+1.66=1.33x | | 1.5+1.66=1.33 | | 5(10x+3)=50x-8 | | 20+4b=6(2b-5) | | a^2+32a=0 | | 2t+4=6 |

Equations solver categories